EXARTICULATION OF THE MAXILLOFACIAL REGION IS A MODERN TECHNOLOGY IN ENDOPROSTHETICS IN PATIENTS WITH SEVERE DISEASES - Akhrorov Alisher Shavkatovich; Hakkulov Ezozbek Komilovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article explores the innovative approach of exarticulation in the maxillofacial region as a cutting-edge technology in endoprosthetics. This technique is particularly significant for patients with severe maxillofacial diseases, providing improved quality of life and functional rehabilitation. The article delves into the methods, results, and implications of exarticulation, supported by a comprehensive literature analysis.